2023
DOI: 10.1177/25151274231190806
|View full text |Cite
|
Sign up to set email alerts
|

Curricular and Extracurricular Entrepreneurial Activities Supporting Entrepreneurial Self-Efficacy and Desirability of Rural Youth

Abstract: Entrepreneurship may be the only viable solution for finding employment in rural areas because of their limited labor markets. However, how curricular and extracurricular entrepreneurial activities can support the entrepreneurial potential of rural youth remains a question. Using a mixed-methods approach, we investigate the impact of curricular and extracurricular entrepreneurial activities on rural adolescents’ entrepreneurial self-efficacy (ESE) and desirability. Our findings show that extracurricular entrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…The development of citizens in a country is based on education at home and training at school. The effect of ES on ESE confirmed in the current study is similar to that reported in South Africa by Neneh (2022) and van der Westhuizen and Goyayi (2019); also, similar to results by Shane and Venkataraman (2000) in a review, Pukkinen et al (2023) in secondary schools students in Finland, in undergraduate students in India (Subhadrammal et al, 2023), Spain (Arranz et al, 2017). Vietnam (Hoang et al, 2021;Nguyen et al, 2021); also, the outcomes are similar to the study of Preedy et al (2020) in professors in United Kingdom and (Elliott et al, 2020) in Canada.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The development of citizens in a country is based on education at home and training at school. The effect of ES on ESE confirmed in the current study is similar to that reported in South Africa by Neneh (2022) and van der Westhuizen and Goyayi (2019); also, similar to results by Shane and Venkataraman (2000) in a review, Pukkinen et al (2023) in secondary schools students in Finland, in undergraduate students in India (Subhadrammal et al, 2023), Spain (Arranz et al, 2017). Vietnam (Hoang et al, 2021;Nguyen et al, 2021); also, the outcomes are similar to the study of Preedy et al (2020) in professors in United Kingdom and (Elliott et al, 2020) in Canada.…”
Section: Discussionsupporting
confidence: 92%
“…This relationship is consistent with the existing literature. Previous research, such as Pukkinen et al (2023), has highlighted the importance of extracurricular support in the development of entrepreneurial self-efficacy. Our results support these findings and contribute to the understanding of how education and activities outside the classroom can influence individuals' confidence in their abilities to undertake green initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…This gap presents an opportunity to answer calls to expand the knowledge of entrepreneurship in all contexts (Baker & Welter, 2018;Welter et al, 2019;Korsgaard et al, 2022), in this instance the rural context. The multiplicity of rural areas (Zografos, 2007;Roos, 2017) makes it necessary for scholars to assess the various dimensions of rurality (Gashi Nulleshi & Tillmar, 2022) in order to advance the relevant theoretical and practical knowledge of rural entrepreneurship (McElwee et al, 2018;Pukkinen, Hytti, Heinonen, & Stenholm, 2023). I therefore systematically reviewed the literature on conceptualizing rural entrepreneurship in the fields of entrepreneurship and rural studies (Paper I).…”
Section: The Field Gap(s)mentioning
confidence: 99%